A clinical score for predicting left ventricular reverse remodelling in patients with dilated cardiomyopathy. (20th January 2021) - Kimura, Yuki; Okumura, Takahiro; Morimoto, Ryota; Kazama, Shingo; Shibata, Naoki; Oishi, Hideo; Araki, Takashi; Mizutani, Takashi; Kuwayama, Tasuku; Hiraiwa, Hiroaki; Kondo, Toru; Murohara, Toyoaki
Abstract: Aims: Left ventricular reverse remodelling (LVRR) is a well‐established predictor of a good prognosis in patients with dilated cardiomyopathy (DCM). The prediction of LVRR is important when developing a long‐term treatment strategy. This study aimed to assess the clinical predictors of LVRR and establish a scoring system for predicting LVRR in patients with DCM that can be used at any institution. Methods and results: We consecutively enrolled 131 patients with DCM and assessed the clinical predictors of LVRR. LVRR was defined as an absolute increase in left ventricular ejection fraction (LVEF) from ≥10% to a final value of >35%, accompanied by a decrease in left ventricular end‐diastolic dimension (LVEDD) ≥ 10% on echocardiography at 1 ± 0.5 years after a diagnosis of DCM. The mean patient age was 50.1 ± 11.9 years. The mean LVEF was 32.2 ± 9.5%, and the mean LVEDD was 64.1 ± 12.5 mm at diagnosis. LVRR was observed in 45 patients (34%) at 1 ± 0.5 years. In a multivariate analysis, hypertension [odds ratio (OR): 6.86; P = 0.002], no family history of DCM (OR: 10.45; P = 0.037), symptom duration <90 days (OR: 6.72; P < 0.001), LVEF <35% (OR: 13.66; P < 0.0001), and QRS duration <116 ms (OR: 5.94; P = 0.005) were found to be independent predictors of LVRR. We scored the five independent predictors according to the ORs (1 point, 2 points, 1 point, 2 points, and 1 point, respectively), and the total LVRR predicting score was calculated by adding these scores. The LVRR rate was stratified by the LVRR predicting score (0–2 points: 0%; 3 points: 6.7%; 4 points: 17.4%; 5 points: 48.2%; 6 points: 79.2%; and 7 points: 100%). The cut‐off value of the LVRR predicting score was >5 in receiver‐operating characteristic curve analysis (area under the curve: 0.89; P < 0.0001; sensitivity: 87%; specificity: 78%). An LVRR predicting score of >5 was an independent predictor compared with the presence of late gadolinium enhancement on cardiovascular magnetic resonance or the severity of fibrosis on endomyocardial biopsy (OR: 11.79; 95% confidence interval: 2.40–58.00; P = 0.002). Conclusions: The LVRR predicting score using five predictors including hypertension, no family history of DCM, symptom duration <90 days, LVEF <35%, and QRS duration <116 ms can stratify the LVRR rate in patients with DCM. The LVRR predicting score may be a useful clinical tool that can be used easily at any institution.